Good Corporate Governance and Audit Quality on Earnings Persistence in Non-Financials Companies from 2020-2023 - Kencana Dewi, Anak Agung Istri Giri; Sukartha, P. D’yan Yaniartha (Dinasti International Journal of Economics, Finance & Accounting, 2026)
In general, when analyzing a company's financial statements, information users primarily focus on earnings data and expect high earnings persistence in a company's financial information. This study aims to examine the relationship between good corporate governance and audit quality on earnings persistence. All companies listed on the Indonesia Stock Exchange from 2020 to 2023 were included in the population of this research. The final sample size consisted of 732 company observations, which were selected using the purposive sampling method. The research data was analyzed using multiple linear regression analysis with STATA as the analysis tool. The findings reveal that good corporate governance has no significant relationship with earnings persistence, while audit quality has a positive relationship with earnings persistence.